HEMICHOREA-HEMIBALLISM IN VARIOUS CONDITIONS: SERIAL CASE REPORTS - Raisa, Neila; Rianawati, Sri Budhi; Kurniawan, Shahdevi Nandar; F, Fahimma; Fitria Nikmahtustsani, Mulika Ade (PERDOSSI (Perhimpunan Dokter Spesialis Saraf Indonesia Cabang Malang) - Indonesian Neurological Association Branch of Malang cooperated with Neurology Residency Program, Faculty of Medicine Brawijaya University, Malang, Indonesia, 2021)
Introduction: Hemichorea-hemiballism (HCHB) is an uncommon movement disorder involved unilateral extremities characterized by irregular, poorly patterned, a continual hyperkinetic involuntary movement disorder in the proximal or distal parts of the body. The acute development of HCHB depends on focal lesions on the contralateral basal ganglia and subthalamic nuclei. Various conditions such as cerebrovascular, neurodegenerative, neoplastic, immunologic, infectious, and metabolic diseases are known as secondary causes of HCHB. This paper aims to compare and discuss the HCHB in various etiologies.Case Reports: Here, we reported 5 cases of HCHB induced by non-ketotic hyperosmolar hyperglycemia (NKKH), thrombotic stroke, and toxoplasmosis cerebral. We compare the admission data, clinical course, imaging, treatment, and outcome of every case.Conclusion: Various hypotheses have been proposed to explain the pathophysiology of HCHB due to these conditions. Principally, the main management for these cases is to determine the etiology and correct the underlying disorder